Digestive Enzyme Activities of Osteochilus vittatus with Spirulina platensis Feed Supplementation in Biofloc System - Yunida, Rizka; Sukardi, Purnama; Simanjuntak, Sorta Basar Ida (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
Osteochilus vittatus is a freshwater fish that needs to be developed because it tastes savory and can be used as a biocleaning agent. Research on the effect of supplementation of Spirulina platensis in nilem fish that is maintained in a biofloc system on digestive enzyme activity has never been done before. The objectives of this study were to determine the effect of S. platensis supplementation on Osteochilus vittatus digestive enzyme activity maintained in the biofloc system and to obtain the most optimum level of S. platensis supplementation in improving the digestive enzymes activity. The study was conducted experimentally with Completely Randomized Design with four treatments and five replications. Osteochilus vittatus were fed with Spirulina platensis level of 0, 2, 4, and 6 g kg-1 for 56 days. Enzyme activity was measured on days 0 and 56 with three kinds of buffer solutions. Amylase and protease activity was analyzed using ANOVA with a confidence level of 95%. The results showed that the highest amylase activity in the liver was 4.764 ± 1.705 U mg-1 protein and proximal intestine was 2.328 ± 0.838 U mg-1 protein. The highest protease activity was found in the liver and proximal intestine with activity of 6.536 ± 0.911 U mg-1 protein and 6.207 ± 2.195 U mg-1protein. Spirulina platensis supplementation level of 6 g kg-1 feed is the most optimum level (p<0.05). Cultivation of fish with S. platensis supplementation in feed can increase enzyme activity and the fish maintenance in biofloc systems can improve water quality.